Masculinization of Nile tilapia (Oreochromis niloticus) using 17α-methyl testosteron - Yuni Widyawati; Muhammad Fakhri; Muhammad Dailami; Nasrullah Bai Arifin (Tomini Journal of Aquatic Science, 2021)
The biological nature of tilapia which causes uncontrolled mating and has an impact on reducing the quality of the fish has become one of the problems in tilapia aquaculture production. 5 times faster than female tilapia. The production of male monosexual tilapia can be obtained in several ways, including the application of low doses of hormones. The purpose of this study was to determine the effectiveness of using low doses of 17α Methyl Testosterone (MT) in immersing tilapia larvae and to obtain superior quality male tilapia results. This study used tilapia larvae that were 1 week old and were stocked in a tank measuring 30x60cm with a dose of MT 1 mg / l, 3 mg / l and 5 mg / l with 3 replications and 1 control. stocking density of 250 birds per cage. Soaking is carried out for 8 hours. The results of immersion of tilapia larvae using MT at a dose of 3 mg / l until the 60th day showed the highest results with the proportion of 72% compared to the untreated dose, 1 mg / l and 5 mg / l. It can be ignored that the use of low doses of 17α Methyl testosterone can affect sex changes in tilapia larvae. The results showed that the dose of 5 mg / l was the best dose with the proportion of male genitalia at 97%.